Slave prices, geography and insolation in 19th century African-American stature - Scott Alan Carson (Center for Economic Studies and ifo Institute (CESifo), 2007)
The use of height data to measure living standards is now a well-established method in the economic literature. Moreover, while much is known about 19th century black legal and material conditions, less is known about how 19th century institutional arrangements were related to black stature. Although modern blacks and whites reach similar terminal statures when brought to maturity under optimal biological conditions, 19th century African-American statures were consistently shorter than whites, indicating a uniquely 19th century phenomenon may have inhibited black stature growth. It is geography and insolation that present the most striking attribute for 19th century black stature, and greater insolation and higher slave prices are documented here to be associated with taller black statures.
Keywords: I32; J15; N31; 330; Farbige Bevölkerung; Gesundheit; Sklaverei; Geographie; USA